The Homonoia Coins of Asia Minor and Ephesians 1:21 - Lotz, John Paul (Tyndale bulletin, 1999)
During the later half of the first century A.D., the political climate in the Greek East was characterised by tensions arising from the competition for titles and status between the leading cities of the eastern provinces, especially in Asia Minor. Ephesus, Smyrna, and Pergamon in particular nurtured tense rivalries over the title of πρώτη Ἀσίας, a designation for primacy in the provincial council of Asia Minor (κοινὸν Ἀσίας). Orators and politicians tried to counter the potentially negative consequences these competitions could have on what political power remained to these Greek cities by exhorting the virtues of ‘political concord’ (ὁμόνοια) in speeches, inscriptions and coins. The homonoia coins of Asia Minor offer us an important insight into the tensions and vicissitudes of city politics in late first century Asia Minor, and help broaden our understanding of the socio-political background and context that Paul and his disciples spoke to. Of special interest will be how the homonoia coins of Asia Minor help us in our interpretation of certain symbols and images that occur in Ephesians 1:21, and how these speak to the persistent struggle to achieve peace and concord in the cities of the Greek East under the Roman ‘peace’, where, according to the writter of the epistle, Caesar and his empire fail to deliver precisely that which Christ and his church are offering: peace and unity.